National Trend of Uroflowmetry, Urodynamic Study and Cystoscopy Considering the Change in the Population Structure in Korea from 2010 to 2015 - Baek, Min Jung; Park, Suyeon; Kim, Ki Hyun; Kim, Yune Hyoun; Kim, Woo Ki; Sun, Hwa Yeon; Kim, Jae Heon (Journal of Korean medical science, 2018)
Although lower urinary tract symptoms (LUTS) show a higher prevalence with age, few studies have reported the trend of these examination tools including uroflowmetry, urodynamic study and cystoscopy. We evaluated the trend of performance of uroflowmetry, urodynamic study and cystoscopy by using National Health Insurance Data from 2010 to 2015. Primary outcome findings included cumulative number of patients per year, cumulative age-standardized patient rate per year and per age group, and correlation between the number of patients per year and the percentage of population per year in each age group. The overall trend for frequency of uroflowmetry and cystoscopy showed an increasing pattern ( < 0.001, respectively) while the trend for frequency of urodynamic study showed a decreasing pattern ( < 0.001). After age standardization, the overall trend showed similar results. Correlation between the number of patients per year and the percentage of population per year showed a positive correlation in the 50s age group and the above 70s age group ( = 0.003 and < 0.01, respectively) on uroflowmetry and in the above 70s age group ( < 0.01) on cystoscopy. Urodynamic study showed negative correlations in the 50s age group and the above 60s age group ( = 0.001 and 0.01, respectively). National trend for frequency of uroflowmetry, urodynamic study and cystoscopy showed a different trend. The increasing trend of uroflowmetry and cystoscopy was related with growth of the aged population. However, urodynamic study showed a decreasing trend regardless of the age group.